2014
DOI: 10.1093/jjco/hyu067
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II/III Trial of Post-operative Chemoradiotherapy Comparing 3-Weekly Cisplatin with Weekly Cisplatin in High-risk Patients with Squamous Cell Carcinoma of Head and Neck: Japan Clinical Oncology Group Study (JCOG1008)

Abstract: A randomized Phase II/III study was launched in Japan to evaluate the non-inferiority of concurrent chemoradiotherapy with weekly cisplatin (40 mg/m 2 ) compared with concurrent chemoradiotherapy with 3-weekly cisplatin (100 mg/m 2 ) for post-operative high-risk patients with locally advanced squamous cell carcinoma of head and neck. This study began in October 2012, and a total of 260 patients will be accrued from 18 institutions within 5 years. The primary endpoint of the Phase II part is proportion of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 20 publications
0
33
0
1
Order By: Relevance
“…It is important to proceed with a long-term follow-up of the chronic toxicities and survival events to explore which treatment could make patients benefit most. Kunieda F et al had launched a randomized phase II/III study in Japan [33], and we are looking forward to make further efforts for the research.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to proceed with a long-term follow-up of the chronic toxicities and survival events to explore which treatment could make patients benefit most. Kunieda F et al had launched a randomized phase II/III study in Japan [33], and we are looking forward to make further efforts for the research.…”
Section: Discussionmentioning
confidence: 99%
“…The ototoxicity and nephrotoxicity of high‐dose cisplatin is well known. Given the similarity between the 40 mg/m 2 weekly and 100 mg/m 2 triweekly patients in our cohorts, it is reasonable to continue to investigate this higher dose weekly regimen and clarity will be looked for from ongoing randomized trials such as JCOG 1008 …”
Section: Resultsmentioning
confidence: 99%
“…However, a small randomized trial (26) showed significantly higher rates of radiation mucositis and overall toxicities for CRT with CDDP at 40 mg/m 2 . To clarify these discrepant findings for the safety and efficacy of 3-weekly and weekly schedules, we are now conducting a Phase II/III trial of postoperative chemoradiotherapy comparing 3-weekly with weekly cisplatin in high-risk patients with squamous cell carcinoma of the head and neck, the JCOG1008 study (UMIN Clinical Trial Registry number: 000009125) (27).…”
Section: Chemotherapymentioning
confidence: 99%